Stimulation of bumetanide-sensitive Na+/K+/Cl- cotransport by different mitogens in synchronized human skin fibroblasts is essential for cell proliferation (The Rockefeller University Press, 1991)
In this study, we examined the role of the bumetanide-sensitive Na+/K+/Cl- cotransport in the mitogenic signal of human skin fibroblast proliferation. The Na+/K+/Cl- cotransport was dramatically stimulated by either fetal calf serum, or by recombinant growth factors, added to quiescent G0/G1 human skin fibroblasts. The following mitogens, FGF, PDGF, alpha-thrombin, insulin-like growth factor-1, transforming growth factor-alpha, and the phorbol ester, 12-O-tetradecanoyl-phorbol-13- acetate, all stimulated the Na+/K+/Cl- cotransport. In addition, all the above mitogens induced DNA synthesis in the synchronized human fibroblasts. In order to explore the role of the Na+/K+/Cl- cotransport in the mitogenic signal, the effect of two specific inhibitors of the cotransport, furosemide and bumetanide, was tested on cell proliferation induced by the above recombinant growth factors. Bumetanide and furosemide inhibited synchronized cell proliferation as was measured by (a) cell exit from the G0/G1 phase measured by the use of flow cytometry, (b) cell entering the S-phase, determined by DNA synthesis, and (c) cell growth, measured by counting the cells. The inhibition by furosemide and bumetanide was reversible, removal of these compounds, completely released the cells from the block of DNA synthesis. In addition, the two drugs inhibited DNA synthesis only when added within the first 2-6 h of cell release. These results indicate that the effect of these drugs is specific, and is not due to an indirect toxic effect. This study clearly demonstrates that the growth factor-induced activation of the Na+/K+/Cl- cotransport plays a major role in the mitogenic signaling pathway of the human fibroblasts.